The Role of Leadership and Motivation of School Headmaster in Improving Teacher Performance - Ahmad Sukandar (UIN Sunan Gunung Djati Bandung, 2018)
This article discusses about role of leadership and motivation of school headmaster in improving teacher performance. By using literature review in education, this article found that teacher is a professional profession where he is required to make every effort to carry out his activities as best he can. The task of the teacher as an educator, teacher and trainer should be able to impact the students. The teacher as one component in teaching and learning activities, has a position that greatly determines the success of learning. The role of the school headmaster is very important and dominant in improving teacher performance, both in increasing competence and work motivation and in building effective work systems and creating a harmonious, safe and pleasant working atmosphere. The efforts of improving the quality of teachers must be continuously carried out by school headmaster in order to improve the performance of teachers into reliable individuals who will advance the school organization. Therefore, we need the ability of the leadership role and motivation of the principal to explore, disseminate, foster and develop the potential of the teacher in order to improve teacher performance in order to achieve educational goals